Practices of Fruit Growing. Applying ontology to taste in Penang and beyond - Leo Mariani (Revue d'ethnoécologie)
Using as a privileged entry point the numb taste — a tingly numbness of the mucous membranes of the mouth, triggered here by a fruit, the durian—this article puts forth an approach to human-food relations encompassing different modes of knowledge, consumption, and production.Steering clear of any theoretical abuse, the approach draws on a detailed ethnographical analysis of this particular taste and the general economy in which it is inscribed, between Malaysia and Singapore, to finally conceptualize various ways of producing and experiencing foods and worlds.The emergence of the numb taste will notably be linked to an agricultural and ontological constraint that the producers and consumers from both countries impose on themselves: against apparent economic good sense, instead of picking them, they wait for the durians to fall from the tree.